Machine learning and deep learning frameworks for the automated analysis of pain and opioid withdrawal behaviors - Bumgarner, Jacob R.; Becker-Krail, Darius D.; White, Rhett C.; Nelson, Randy J. (Frontiers in Neuroscience, 2022)
The automation of behavioral tracking and analysis in preclinical research can serve to advance the rate of research outcomes, increase experimental scalability, and challenge the scientific reproducibility crisis. Recent advances in the efficiency, accuracy, and accessibility of deep learning and machine learning frameworks are enabling this automation. As the ongoing opioid epidemic continues to worsen alongside increasing rates of chronic pain, there are ever-growing needs to understand opioid use disorders and identify non-opioid therapeutic options for pain. In this review, we examine how these related needs can be advanced by the development and validation of deep and machine learning resources for automated pain and withdrawal behavioral tracking. We aim to emphasize the utility of these tools for automated behavioral analysis, and we argue that currently developed models should be deployed to address novel questions in the fields of pain and opioid use disorder research.